Novel Applications of Nanotechnology in Controlling HIV and HSV Infections - Akilesh M, Sai; Wadhwani, Ashish (Current Drug Research Reviews, 2021)
Infectious diseases have been prevalent for many decades and viral pathogens have caused global health crises and economic meltdown on a devastating scale. The high occurrence of novel viral infections in recent years, in spite of the progress achieved in the field of pharmaceutical sciences, defines the critical need for newer and more effective antiviral therapies and diagnostics. The incidence of multi-drug resistance and adverse effects due to the prolonged use of anti-viral therapy is also a major concern. Nanotechnology offers a cutting edge platform for the development of novel compounds and formulations for biomedical applications. The unique properties of nano-based materials can be attributed to the multi-fold increase in the surface to volume ratio at the nano-scale, tunable surface properties of charge and chemical moieties. Idealistic pharmaceutical properties such as increased bioavailability and retention times, lower toxicity profiles, sustained- release formulations, lower dosage forms and most importantly, targeted drug delivery can be achieved through the approach of nanotechnology. The extensively researched nano-based materials are metal and polymeric nanoparticles, dendrimers and micelles, nano-drug delivery vesicles, liposomes and lipid-based nanoparticles. In this review article, the impact of nanotechnology on the treatment of Human Immunodeficiency Virus (HIV) and Herpes Simplex Virus (HSV) viral infections during the last decade is outlined.
Keywords: Nanotechnology